2000
DOI: 10.5326/15473317-36-4-359
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative risk factors for puppies delivered by cesarean section in the United States and Canada

Abstract: The purpose of this study was to evaluate perioperative risk factors affecting neonatal survival after cesarean section. Data from 807 cesarean-derived litters (3,908 puppies) was submitted by 109 practices in the United States and Canada. Survival rates immediately, two hours, and seven days after delivery were 92% (n=3,127), 87% (n=2,951), and 80% (n=2,641), respectively, for puppies delivered by cesarean section (n=3,410) and were 86% (n=409), 83% (n=366), and 75% (n=283), respectively, for puppies born nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
3
18

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(133 citation statements)
references
References 9 publications
3
96
3
18
Order By: Relevance
“…Fluid therapy is recommended as a standard for CS in bitches [8][9][10][11][12][13][14]. Fluids are given to correct any fluid and electrolyte deficits, acid-base balances, the hypotensive effects of anaesthesia and maintain cardiac output and uterine blood flow [8].…”
Section: Introductionmentioning
confidence: 99%
“…Fluid therapy is recommended as a standard for CS in bitches [8][9][10][11][12][13][14]. Fluids are given to correct any fluid and electrolyte deficits, acid-base balances, the hypotensive effects of anaesthesia and maintain cardiac output and uterine blood flow [8].…”
Section: Introductionmentioning
confidence: 99%
“…Anesthetic induction with propofol iv followed by isoflurane maintenance was reported to 64 result in improved puppy vigor and newborn survival rates compared to other general 65 anesthetic protocols and was considered almost equal to epidural anesthesia [6][7][8]. 66…”
Section: Objective: To Compare Alfaxalone and Propofol As Anesthetic mentioning
confidence: 99%
“…Both maternal lethargy and 57 reduced neonatal vitality during the critical first postoperative hours result in reduced 58 colostrum intake and increased mortality rate of the puppies [3, [5][6][7]. Currently, many 59 veterinary clinics and practices use an anesthetic protocol with propofol induction followed 60 by isoflurane maintenance, with or without additional sedatives and / or analgesics.…”
Section: Objective: To Compare Alfaxalone and Propofol As Anesthetic mentioning
confidence: 99%
See 1 more Smart Citation
“…Newborn puppy mortality for normal deliveries is 5.55%, significantly lower than that for dystocia deliveries, which is 33% (Moon et al, 2001). In cases of elective or emergency caesarean section, Moon et al (2000) reported neonatal death rates of between 6-11%.…”
Section: Neonatal Assessmentmentioning
confidence: 99%